A bright future for bioluminescent imaging in viral research. (February 2015) - Coleman, Stewart M; McGregor, Alistair
SUMMARY : Bioluminescence imaging (BLI) has emerged as a powerful tool in the study of animal models of viral disease. BLI enables real-time in vivo study of viral infection, host immune response and the efficacy of intervention strategies. Substrate dependent light emitting luciferase enzyme when incorporated into a virus as a reporter gene enables detection of bioluminescence from infected cells using sensitive charge-coupled device (CCD) camera systems. Advantages of BLI include low background, real-time tracking of infection in the same animal and reduction in the requirement for larger animal numbers. Transgenic luciferase-tagged mice enable the use of pre-existing nontagged viruses in BLI studies. Continued development in luciferase reporter genes, substrates, transgenic animals and imaging systems will greatly enhance future BLI strategies in viral research.